RNA base-pairing complexity in living cells visualized by correlated chemical probing - Mustoe, Anthony M. (Proc Natl Acad Sci U S A, 2019)
RNA structure and dynamics are critical to biological function. However, strategies for determining RNA structure in vivo are limited, with established chemical probing and newer duplex detection methods each having deficiencies. Here we convert the common reagent dimethyl sulfate into a useful probe of all 4 RNA nucleotides. Building on this advance, we introduce PAIR-MaP, which uses single-molecule correlated chemical probing to directly detect base-pairing interactions in cells. PAIR-MaP has superior resolution compared to alternative experiments, can resolve multiple sets of pairing interactions for structurally dynamic RNAs, and enables highly accurate structure modeling, including of RNAs containing multiple pseudoknots and extensively bound by proteins. Application of PAIR-MaP to human RNase MRP and 2 bacterial messenger RNA 5′ untranslated regions reveals functionally important and complex structures undetected by prior analyses. PAIR-MaP is a powerful, experimentally concise, and broadly applicable strategy for directly visualizing RNA base pairs and dynamics in cells.